Almost Periodic Solutions of Nonlinear Equations that are not Necessarily Almost Periodic in Bochner’s Sense - Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We introduce a new class of almost periodic operators and establish conditions for the existence of almost periodic solutions of nonlinear equations that are not necessarily almost periodic in Bochner’s sense.